If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 6) + -9 = 40 + -5x + -1 + 13 Reorder the terms: 8(6 + x) + -9 = 40 + -5x + -1 + 13 (6 * 8 + x * 8) + -9 = 40 + -5x + -1 + 13 (48 + 8x) + -9 = 40 + -5x + -1 + 13 Reorder the terms: 48 + -9 + 8x = 40 + -5x + -1 + 13 Combine like terms: 48 + -9 = 39 39 + 8x = 40 + -5x + -1 + 13 Reorder the terms: 39 + 8x = 40 + -1 + 13 + -5x Combine like terms: 40 + -1 = 39 39 + 8x = 39 + 13 + -5x Combine like terms: 39 + 13 = 52 39 + 8x = 52 + -5x Solving 39 + 8x = 52 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 39 + 8x + 5x = 52 + -5x + 5x Combine like terms: 8x + 5x = 13x 39 + 13x = 52 + -5x + 5x Combine like terms: -5x + 5x = 0 39 + 13x = 52 + 0 39 + 13x = 52 Add '-39' to each side of the equation. 39 + -39 + 13x = 52 + -39 Combine like terms: 39 + -39 = 0 0 + 13x = 52 + -39 13x = 52 + -39 Combine like terms: 52 + -39 = 13 13x = 13 Divide each side by '13'. x = 1 Simplifying x = 1
| -2+4(x-4)=13x+2-9x | | -(3z-4)=6z-3(3z+2) | | 0.8x-0.4(9-3x)=-0.2(x-4) | | 31-5(x+1)=x | | sqrt(x-2)=x-3 | | x+4y=-7 | | 4t/-9=-5 | | 5/54-2/24-3/96 | | x^2+4x=286 | | 5-2w/3=10 | | 2=12x^2+2x | | -16t^2+32t+256=0 | | x^2+15x=76 | | (2x-3)(3x+9)= | | 9(t-2)+3t=6(2t+4)-9 | | 2x=12x^2+2x | | 2x^3+20x^2+48=0 | | 7y+x=26 | | 16x-3+3x-5=-3x-63 | | 5(9x+4)=290 | | (300-x)100=110 | | 4(3n+4)=2(6n+8) | | y-9x=22 | | 8(10x-9)=488 | | X=11y-4 | | 12/36=4/c | | 0.85x+.05(10-x)=.10(-107) | | 11y-4=x | | 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 |